Assessing the effect of anesthetic gas mixtures on hyperpolarized 13C pyruvate metabolism in the rat brain. Issue 3 (25th April 2022) - Healicon, Richard; Rooney, Catriona H. E.; Ball, Vicky; Shinozaki, Ayaka; Miller, Jack J.; Smart, Sean; Radford‐Smith, Daniel; Anthony, Daniel; Tyler, Damian J.; Grist, James T.
Abstract : Purpose: To determine the effect of altering anesthetic oxygen protocols on measurements of cerebral perfusion and metabolism in the rodent brain. Methods: Seven rats were anesthetized and underwent serial MRI scans with hyperpolarized [1– 13 C]pyruvate and perfusion weighted imaging. The anesthetic carrier gas protocol used varied from 100:0% to 90:10% to 60:40% O2 :N2 O. Spectra were quantified with AMARES and perfusion imaging was processed using model‐free deconvolution. A 1‐way ANOVA was used to compare results across groups, with pairwise t tests performed with correction for multiple comparisons. Spearman's correlation analysis was performed between O2 % and MR measurements. Results: There was a significant increase in bicarbonate:total 13 C carbon and bicarbonate: 13 C pyruvate when moving between 100:0 to 90:10 and 100:0 to 60:40 O2 :N2 O % (0.02 ± 0.01 vs. 0.019 ± 0.005 and 0.02 ± 0.01 vs. 0.05 ± 0.02, respectively) and (0.04 ± 0.01 vs. 0.03 ± 0.01 and 0.04 ± 0.01 vs. 0.08 ± 0.02, respectively). There was a significant difference in 13 C pyruvate time to peak when moving between 100:0 to 90:10 and 100:0 to 60:40 O2 :N2 O % (13 ± 2 vs. 10 ± 1 and 13 ± 2 vs. 7.5 ± 0.5 s, respectively) as well as significant differences in cerebral blood flow (CBF) between gas protocols. Significant correlations between bicarbonate: 13 C pyruvate and gas protocol (ρ = −0.47), mean transit time and gas protocol (ρ = 0.41) and 13 C pyruvate time‐to‐peak and cerebral blood flow (ρ = −0.54) were also observed. Conclusions: These results demonstrate that the detection and quantification of cerebral metabolism and perfusion is dependent on the oxygen protocol used in the anesthetized rodent brain.